ANALYSIS OF LOCAL GOVERNMENT MOBILE GOVERNMENT APPLICATION MAPPING IN EAST JAVA PROVINCE - Binti azizatun Nafi'ah; Ratih Pandu Mustikasari; Katerina Bataha (DIA: Jurnal Administrasi Publik, 2021)
Currently, e-government has migrated to m-government. During the COVID-19 pandemic, mobile government is more popular with the public where the recommendations for maintaining distance and staying at home can be implemented while being able to access public services. This study presents the mapping of local government applications and identifies the categorization conditions for the mapping of local government applications in the province of East Java. Researchers used a quantitative approach. Data collection uses secondary data where application data is obtained from the Android smartphone play store. After the data was collected, the researcher used descriptive statistical analysis to map the quantity of applications made by the regional government of East Java province. Then, classify application categories based on Ganapati (2015), namely enterprise-focused apps and citizen-focused apps. This mapping research and application category classification is intended to be a reference for other local governments in the development of m-government. In public administration, this study is useful in the development of m-government science. The results found are regional governments throughout East Java Province have a total of 362 m-governance applications. The majority of applications (86%) are focused on community service and the rest are business-oriented. The highest category in productivity applications and applications for communication. Meanwhile, 14% of applications focus on business activities.